Local Features in the Decoration of the Mound Space of the Burial Monuments of Petrovka Culture - Fricke Polina A. (Поволжская археология, 2020)
The paper analyzes the attributes of the decoration of the barrow space in the monuments of the Petrovka culture. In the context of the wide geographical area, the monuments of the Petrovka culture demonstrate variability in terms of the barrow space decoration. This feature can be accounted for by the territorial and temporal framework, selection of the most suitable burial techniques, or errors in the transfer of cultural information. Many elements of the funeral rite have local features corresponding to those stereotypes which were selected during their evolution. The author considers such features as the presence of a moat and its dimensions, the presence of a clay platform, and the location of grave pits and altars in the barrow space. The analysis results have allowed to subdivide the funerary monuments of Petrovk archaeological culture into the following two local areas: western – in the valleys of the Tobol and Uy rivers, and eastern – in the valley of the Ishim river. They have a number of distinctive features, some of which are analyzed in the papers. The issues of variability of funeral practices are not limited to the elements discussed in this paper, and they remain relevant and require further research.